Customer Satisfaction of Beauty n Hair Salon in Ciayumajakuning through Brand Experience and Perceived Value of Makarizo - Nanda Leopinda Putri; Ica Cahyani; Misbak Misbak; Tiara Muthiarsih (CV. AFDIFAL MAJU BERKAH, 2025)
The purpose of this study was to determine how customer satisfaction with Makarizo products in the Ciayumajakuning area is influenced by perceived value and brand experience. The tight competition in the hair care sector, which requires innovation and provides high-quality goods at competitive prices, is the background of this study. An online questionnaire was used in this quantitative study to collect data from 200 Makarizo consumers who were at least 17 years old and living in Cirebon, Indramayu, Majalengka, Kuningan. Multiple linear regression data analysis with SPSS. Based on the findings, each statement item related to the variables of perceived value, consumer satisfaction, and brand experience is considered valid and reliable. In addition, there are no signs of multicollinearity and the results of the linearity test indicate a substantial relationship between the independent and dependent variables. It is expected that this study will help the Makarizo hair care business especially in increasing customer satisfaction by managing perceived value and brand experience effectively.